Resin grinding wheel material, preparation method thereof and heavy-load grinding wheel

By coating the powder on the surface of abrasive particles and using melt blending technology to prepare resin grinding wheel materials, the problem of uneven flying powder and forming structure during heavy-load grinding wheel preparation is solved, and the uniformity and performance of grinding wheel structure are improved.

CN119910578APending Publication Date: 2025-05-02SHANDONG SHENGQUAN NEW MATERIALS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510044697.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the preparation process of heavy-load grinding wheels in the prior art, when the abrasive and powder are mixed and put into the mold, it is easy to cause uneven flying powder and molding structure, which affects the overall performance of the grinding wheel.

Method used

By covering the powder on the surface of the abrasive particles, a resin grinding wheel material is formed, and the powder is prepared by melt blending technology, and abrasive particles coated with the powder are obtained through mechanical dispersion and screening, avoiding the problems of uneven dispersion and agglomeration during the mixing process.

Benefits of technology

It effectively reduces the problem of uneven adhesion and dispersion of powder, improves the structure of the grinding wheel, and improves the overall performance of the grinding wheel, including improving the rotation strength and impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238149750000181
    Figure BDA0005238149750000181
  • Figure BDA0005238149750000191
    Figure BDA0005238149750000191
  • Figure BDA0005238149750000221
    Figure BDA0005238149750000221
Patent Text Reader

Abstract

The invention discloses a resin grinding wheel material and a preparation method thereof and a heavy-load grinding wheel, the resin grinding wheel material comprises a grinding material and powder coating the surface of the grinding material, the powder comprises thermosetting resin particles and inorganic filler, and the powder is obtained by melting, blending and granulating the thermosetting resin particles and the inorganic filler. The grinding materials are heated and then mixed into the powder, the high temperature of the grinding materials melts and adheres resin in the powder to the surfaces of the grinding materials to form coating materials, the grinding materials with different granularities can be coated and mixed respectively, the uniformity of the mixed materials is guaranteed, powder flying is effectively avoided, the uniformity of the manufactured structure of the grinding wheel is better, and the hardness and the impact strength are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of abrasive materials and grinding tools, and specifically relates to a resin grinding wheel material and a preparation method thereof, and a heavy-load grinding wheel. Background Art

[0002] Heavy-duty grinding wheels are designed to withstand high-intensity grinding operations and are widely used in the steel industry for surface cleaning of steel ingots, billets, plates, bars and various castings. They are characterized by high operating speed, high grinding pressure and excellent grinding efficiency. With the progress of the steel industry and the development of high-efficiency grinding technology, resin-bonded grinding wheels have gradually replaced ceramic-bonded grinding wheels and become the mainstream due to their excellent rotational strength and impact resistance.

[0003] The core components of the resin heavy-duty grinding wheel are high-strength polymer resin binder, powdered auxiliary materials, and zirconium corundum abrasives. Its preparation process involves multiple steps such as mixing, hot pressing and heat curing. In the mixing stage, dry room temperature mixing technology is traditionally used to try to promote the adhesion of resin powder to abrasives by adding trace amounts of wetting agents or coupling agents. However, this process has limitations: due to the limited amount of wetting agents or coupling agents added, it is difficult for resin powder to adhere evenly and firmly to the surface of the abrasive; coupled with the difference in abrasive particle size and the uneven density between the abrasive and the dispersed powder, the final grinding wheel has an uneven structure and many defects, which affects the overall performance of the grinding wheel. Summary of the invention

[0004] In order to solve the technical problems of flying powder and uneven molding structure when the abrasive and powder are mixed and put into the mold during the preparation of heavy-duty grinding wheels in the prior art, the present application provides a resin grinding wheel material on the one hand, which is formed by wrapping the powder on the surface of the abrasive particles, and can effectively reduce the adhesion and uneven dispersion of the powder when processing the grinding wheel. Other aspects of the present application also provide a preparation method of the resin grinding wheel material, and a heavy-duty grinding wheel and method prepared using the resin grinding wheel material.

[0005] In one aspect of the present application, a resin grinding wheel material is provided, comprising abrasive particles and powder coated on the surface of the abrasive particles, wherein the powder raw material comprises thermosetting resin particles and inorganic filler.

[0006] In one embodiment, the powder is obtained by melt-blending and granulating the thermosetting resin particles and the inorganic filler.

[0007] In one embodiment, the melt blending temperature is between the melt softening temperature and the thermal curing temperature of the thermosetting resin particles.

[0008] In one embodiment, the resin grinding wheel material comprises 100 parts of abrasive particles and 40 to 70 parts of powder by weight.

[0009] In one embodiment, the resin grinding wheel material includes 100 parts of abrasive particles and 55 parts of powder by weight.

[0010] In one embodiment, the mass ratio of the thermosetting resin particles to the inorganic filler is 10:20-50.

[0011] In one embodiment, the mass ratio of the thermosetting resin particles to the inorganic filler is 10:30.

[0012] In one embodiment, the particle size of the abrasive particles is 6-24#, the particle size D50 of the thermosetting resin particles is 8-30 μm, and the particle size D50 of the inorganic filler is 7-20 μm.

[0013] In one embodiment, the particle size of the abrasive particles is 6-24#, the particle size D50 of the thermosetting resin particles is 10-20 μm, and the particle size D50 of the inorganic filler is 8-15 μm.

[0014] In one embodiment, the abrasive particles are selected from one or more of brown corundum, white corundum, black silicon carbide, green silicon carbide, cubic boron nitride, chrome corundum, single crystal corundum, microcrystalline corundum, zirconium corundum, and ceramic corundum.

[0015] In one embodiment, the abrasive particles are selected from zirconium corundum.

[0016] In one embodiment, the thermosetting resin particles are selected from one or more of phenolic resin, epoxy resin, polyphthalonitrile resin, polyurethane resin, polyimide resin and aralkylphenolic resin.

[0017] In one embodiment, the thermosetting resin particles are selected from phenolic resins.

[0018] In one embodiment, the inorganic filler is selected from one or more of iron sulfide, cryolite, potassium sulfate, calcium oxide, hemihydrate gypsum powder, corundum, silicon carbide powder, potassium fluoroborate, glass fiber, copper slag, inorganic oxides, zeolite, magnesium oxide, chromium oxide, graphite, molybdenum disulfide, and zinc oxide.

[0019] In one embodiment, the inorganic filler is selected from a mixture of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber, and the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 100:10-60:30-80:40-60:40-60.

[0020] In one embodiment, the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 100:40-50:60-70:45-55:45-55.

[0021] In another aspect of the present application, a method for preparing the resin grinding wheel material is provided, comprising the following steps:

[0022] Adding a curing agent to the thermosetting resin particles and the inorganic filler, heating them to a first temperature for melting and blending, and granulating to obtain a powder; the first temperature is between the melting point of the thermosetting resin and the thermal curing temperature;

[0023] The powder is put into the abrasive at the third temperature, stirred until the powder is coated on the surface of the abrasive, cooled to a fourth temperature and broken up to obtain abrasive particles coated with the powder; the third temperature is between the melting point and the thermal curing temperature of the thermosetting resin and higher than the first temperature; the fourth temperature is equal to or lower than the melting point of the thermosetting resin.

[0024] In one embodiment, the curing agent accounts for 5 to 15% of the mass of the thermosetting resin particles. Preferably, the curing agent accounts for 10 to 12% of the mass of the thermosetting resin particles.

[0025] In one embodiment, the curing agent is selected from one or more of hexamethylenetetramine, polyoxymethylene, alkaline thermosetting resin, and epoxy resin.

[0026] In one embodiment, the curing agent is selected from hexamethylenetetramine.

[0027] In one embodiment, mechanical or air flow breaking is adopted, and then sifting is performed to obtain abrasive particles coated with powder.

[0028] In one embodiment, the third temperature is 10-50° C. higher than the first temperature.

[0029] In one embodiment, the fourth temperature is equal to the melting point of the thermosetting resin particles.

[0030] In one embodiment, the sieve aperture is 2 to 12 meshes, preferably 4 to 8 meshes.

[0031] In one embodiment, the abrasive is heated to the second temperature and then cooled to the third temperature.

[0032] In one embodiment, the second temperature is 160-190°C.

[0033] In one embodiment, the thermosetting resin particles are phenolic resin, and the first temperature is 100-120°C.

[0034] In one embodiment, the thermosetting resin particles are phenolic resin, and the third temperature is 130-150°C.

[0035] In another aspect of the present application, a heavy-load grinding wheel is provided, wherein the raw material of the heavy-load grinding wheel includes the resin grinding wheel material.

[0036] In another aspect of the present application, a method for preparing the heavy-load grinding wheel is also provided, comprising the following steps:

[0037] Pre-pressing the resin grinding wheel material to obtain a primary blank;

[0038] Preheating the preformed blank to 80-100° C., heating it to 180-195° C., and pressing it to obtain a formed grinding wheel;

[0039] The molded grinding wheel is subjected to thermal curing treatment to obtain the heavy-load grinding wheel.

[0040] In one embodiment, the pre-pressing pressure is 4-10 MPa.

[0041] In one embodiment, the preformed blank is preheated from room temperature to 80-100° C. within 20-60 min.

[0042] In one embodiment, the pressing pressure of the molding grinding wheel is 10 to 20 MPa;

[0043] In one embodiment, the molded grinding wheel is made by pressing at a pressure of 10 to 20 MPa for 60 to 120 minutes.

[0044] In one embodiment, the curing procedure of the heat curing treatment is: room temperature; heating to 80°C for 60 minutes, keeping warm for 60 minutes; heating to 120°C for 60 minutes, keeping warm for 120 minutes; heating to 160°C for 60 minutes, keeping warm for 120 minutes; heating to 185°C for 60 minutes, keeping warm for 600 minutes; cooling to 80°C for 300 minutes.

[0045] The beneficial effects of this application are:

[0046] The present application provides a resin grinding wheel material, which is formed by coating powder on the surface of an abrasive. When preparing the grinding wheel, the resin grinding wheel material is directly used for pressing, thereby avoiding the mixing process during the preparation process. In addition, when preparing the grinding wheel, the coating structure can effectively avoid problems such as uneven dispersion and agglomeration of powder and abrasive, thereby making the powder and abrasive evenly distributed, improving the organizational structure of the grinding wheel, and thus improving the overall performance of the grinding wheel. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1The cross-sectional morphology of the grinding wheel of Application Example 8 of this application and Comparative Application Example 5. DETAILED DESCRIPTION

[0048] The technical scheme of the present application will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are some embodiments of the present application, rather than all embodiments, and are only used to illustrate the present application, and should not be considered as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be obtained by commercial purchase.

[0049] In one embodiment of the present application, a resin grinding wheel material is provided, the main purpose of which is to overcome the problems of uneven mixing of abrasives, resin materials and inorganic fillers and fly ash in the preparation process of the prior art. The resin grinding wheel material comprises abrasive particles and a powder coated on the surface of the abrasive particles, the powder raw material comprises thermosetting resin particles and inorganic fillers, and the thermosetting resin particles and inorganic fillers are melt-blended and granulated to obtain the powder.

[0050] In this application, coating refers to uniformly covering a certain material (powder) on the surface of another material (abrasive particles). This coating process can enhance the performance of the abrasive particles, such as improving wear resistance, hardness or improving its bonding with the substrate.

[0051] In this application, a thermosetting resin is a resin that cures (i.e., hardens) to an insoluble, infusible solid material upon heating. Such resins can soften and flow when initially heated so that they can be mixed with other materials or formed, but once cured, they cannot be re-softened by heating. Thermosetting resin pellets are a granular form of such resins that are convenient for storage, transportation, and processing.

[0052] In this application, melt blending refers to the process of mixing two or more materials in a molten state. Thermosetting resin particles and inorganic fillers are heated to a molten state and then mixed uniformly by mechanical stirring or other means. This process helps ensure that the thermosetting resin and inorganic filler are evenly distributed, thereby improving the performance of the final product.

[0053] In the present application, granulation is the process of processing a uniformly mixed material into a granular product through a specific process (such as extrusion, tableting, cutting, etc.). The thermosetting resin and inorganic filler mixture after melt blending is processed into powder particles. These powder particles are then coated on the surface of abrasive particles for manufacturing resin grinding wheel materials.

[0054] The resin grinding wheel material tightly wraps the powder layer formed by pre-mixed thermosetting resin particles and inorganic fillers on the surface of the abrasive particles. This process ensures that each abrasive particle is covered with a uniform and dense powder layer, so that in the subsequent grinding wheel pressing and molding process, the distribution between the abrasive, resin and inorganic filler reaches an unprecedented uniformity. This micronized processing method greatly reduces the local accumulation of inorganic fillers, and also effectively solves the problem of uneven dispersion of abrasive particles, thereby significantly improving the structural uniformity and overall performance of the internal organization of the grinding wheel. In addition, since the thermosetting resin particles and inorganic fillers are directly adhered to the surface of the abrasive particles instead of being randomly distributed in the traditional mixing process, this design fundamentally reduces the fine particles (i.e., fly ash) generated by material separation or vibration during the grinding wheel preparation process. The reduction of fly ash not only improves the working environment and reduces the health risks to operators, but also improves the purity and quality consistency of the final product.

[0055] In some embodiments, the temperature of melt blending is between the melt softening temperature and the heat curing temperature of the thermosetting resin particles. Thermosetting resin particles begin to soften when heated to a certain temperature, and this temperature is called the melt softening temperature. At the melt softening temperature, the viscosity of the thermosetting resin particles decreases, and the fluidity is enhanced, which is convenient for mixing with other materials (such as inorganic fillers). However, it should be noted that no curing reaction occurs at this time, and it can still be reshaped through further heating and cooling processes. The heat curing temperature is the temperature at which the thermosetting resin particles begin to undergo a curing reaction. Once the temperature reaches or exceeds this threshold, the thermosetting resin particles will begin to cross-link and cure to form a stable network structure. The cured resin has excellent physical and chemical properties, such as hardness, heat resistance, corrosion resistance, etc. When preparing resin grinding wheel materials, the selection of the melt blending temperature is crucial. This temperature must be between the melt softening temperature and the heat curing temperature of the thermosetting resin particles to ensure that the resin particles can be fully softened and mixed evenly with the inorganic filler, while avoiding premature curing reactions, which affects the further coating effect of the abrasive particles. Specifically, if the melt blending temperature is too low, the resin particles may not be fully softened, resulting in uneven mixing and affecting the performance of the final product. When the melt blending temperature is too high, close to or exceeding the thermal curing temperature of the thermosetting resin particles, on the one hand, the resin particles will begin to undergo a curing reaction, and the resin particles during the curing process will quickly form a cross-linked network structure, resulting in a sharp increase in viscosity. This not only makes mixing difficult, but may also cause the mixing equipment to be damaged by excessive stress; on the other hand, once the resin particles begin to cure, this process is irreversible, which means that when these cured thermosetting resin particles are further coated with abrasive particles, they can no longer soften to form a good coating layer. Due to the high hardness and brittleness of the cured resin particles, it is difficult for them to tightly bond with the abrasive particles, resulting in coating failure.

[0056] In some embodiments, the resin grinding wheel material includes 100 parts of abrasive and 40 to 70 parts of powder by weight. Preferably, the resin grinding wheel material includes 100 parts of abrasive and 55 parts of powder by weight. Specifically, when 100 parts of the abrasive are included by weight, the powder can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, and 70 parts by weight. Abrasives are the main components of grinding wheels, and their dosage is directly related to the grinding ability and wear characteristics of the grinding wheel. The high proportion of abrasives ensures that the grinding wheel can effectively remove the workpiece material during the grinding process while maintaining the sharpness and grinding efficiency of the grinding wheel; the amount of powder plays an important role in the structural strength, hardness and thermal stability of the grinding wheel. The appropriate use of powder can ensure that the abrasive particles are evenly wrapped to form a solid grinding wheel structure, thereby improving the durability and impact resistance of the grinding wheel.

[0057] In some embodiments, the mass ratio of the thermosetting resin particles to the inorganic filler is 10:20 to 50, preferably, the mass ratio of the thermosetting resin particles to the inorganic filler is 10:30. Specifically, the mass ratio of the thermosetting resin particles to the inorganic filler can be 10:20, 10:22, 10:24, 10:26, 10:28, 10:30, 10:32, 10:34, 10:36, 10:38, 10:40, 10:42, 10:44, 10:46, 10:48, 10:50. By limiting the amount of the thermosetting resin particles and the inorganic filler, the powder formed by the thermosetting resin particles and the inorganic filler can be evenly and densely coated on the surface of the abrasive, ensuring the bonding strength with the abrasive, while enhancing the strength of the resin grinding wheel material.

[0058] In some embodiments, the particle size of the abrasive particles is 6-24#, preferably, the particle size of the abrasive particles is 8-20#. Specifically, the particle size of the abrasive particles can be 6#, 7#, 8#, 9#, 10#, 11#, 12#, 13#, 14#, 15#, 16#, 17#, 18#, 19#, 20#. The particle size D50 of the thermosetting resin particles is 8-30μm, preferably, the particle size D50 of the thermosetting resin particles is 10-20μm. Specifically, the particle size D50 of the thermosetting resin particles can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm. The particle size D50 of the inorganic filler is 7-20μm, preferably, the particle size D50 of the inorganic filler is 8-15μm. Specifically, the particle size D50 of the inorganic filler can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm.

[0059] In the present application, "particle size" refers to the size or coarseness of abrasive particles, which is specifically measured by the screening method of the US standard sieve (ASTME11-09 or other equivalent international standards). Here, the particle size is represented by the "#" sign, which represents the number of mesh holes per inch on the sieve in the US standard sieve system. The larger the value, the finer the mesh holes and the smaller the particles; the smaller the value, the coarser the mesh holes and the larger the particles. Specifically, the particle size of the abrasive particles described in the present invention is limited to the range of 6# to 24#. This means that the abrasive particles can pass through the 6# sieve (i.e., there are 6 mesh holes per inch of the sieve, corresponding to larger particles) but cannot pass through the 24# sieve (i.e., there are 24 mesh holes per inch of the sieve, corresponding to smaller particles), and its particle size is between the two.

[0060] In this application, grain size, also known as particle size or diameter, refers to the size of a material particle. When a certain physical property or physical behavior of the measured particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. For spherical particles, their size is usually directly expressed in diameter. For non-spherical particles, the concept of equivalent particle size is used to describe their size. Since the shape of actual particles is usually non-spherical, it is difficult to directly express their size in terms of diameter. Therefore, in the field of particle size testing, equivalent particle size is usually used to describe the size of non-spherical particles. Equivalent particle size means that when a particle's physical property or physical behavior is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size of the measured particle. The particle size D50 of this application is the volume median diameter or median particle size, which refers to the diameter of the particle volume corresponding to when the cumulative volume percentage reaches 50% in the particle size distribution diagram. Simply put, this means that among all the particles, half of the particles have a diameter less than or equal to D50, and the other half have a diameter greater than or equal to D50. Measuring D50 usually requires the use of particle size analysis equipment, such as a laser particle size analyzer or a sedimentation particle size analyzer. These devices infer the size distribution of particles by detecting the physical properties of the particles (such as light scattering intensity, sedimentation rate, etc.), and calculate the D50 value accordingly. In this application, the particle size D50 mentioned is determined by Malvern's Mastersizer 3000 particle size tester, and the range of D50 refers to the interval covered by the minimum and maximum particle diameters measured by the instrument.

[0061] The particle size of the abrasive particles needs to form a good matching relationship with the particle size of the thermosetting resin particles and the inorganic filler. Abrasive particles with appropriate particle size can ensure uniform distribution in the resin matrix, while the thermosetting resin particles and the inorganic filler can tightly surround the abrasive particles to form a continuous and dense coating layer. This good particle size matching is the basis for achieving efficient coating; by finely controlling the particle size of each component, the uniformity of the coating layer can be significantly improved. Thermosetting resin particles and inorganic fillers can evenly penetrate into the gaps between the abrasive particles to avoid the formation of gaps or defects, thereby enhancing the integrity and continuity of the coating layer. This uniform coating effect helps to improve the wear resistance and service life of the grinding wheel.

[0062] In certain embodiments, the abrasive particles are selected from one or more of brown corundum, white corundum, black silicon carbide, green silicon carbide, cubic boron nitride, chrome corundum, single crystal corundum, microcrystalline corundum, zirconium corundum, and ceramic corundum. Preferably, the abrasive particles are selected from zirconium corundum. Zirconium corundum is a high-performance abrasive material with extremely high hardness, good wear resistance and excellent thermal stability. These characteristics enable zirconium corundum to maintain a sharp cutting edge during the grinding process, effectively remove materials on the surface of the workpiece, and reduce wear and heat accumulation, thereby extending the service life of the grinding wheel and maintaining stable grinding performance. Zirconium corundum is selected as an abrasive particle not only because of its excellent performance in hardness, wear resistance and thermal stability, but also because it can form a good combination with thermosetting resin particles and inorganic fillers to ensure the stability and reliability of the grinding wheel structure. In addition, zirconium corundum also has good self-sharpening properties, can continuously expose new cutting edges during the grinding process, and maintain high grinding efficiency.

[0063] In some embodiments, the thermosetting resin particles are selected from one or more of phenolic resin, epoxy resin, polyphthalonitrile resin, polyurethane resin, polyimide resin and aralkylphenolic resin. Epoxy resin has good bonding properties and mechanical strength, and is suitable for grinding wheel materials requiring high strength and chemical corrosion resistance; polyimide resin has excellent comprehensive properties, including high temperature resistance, radiation resistance, chemical corrosion resistance and good electrical insulation. Among grinding wheel materials, polyimide resin can provide excellent heat resistance and mechanical properties, and is suitable for high-performance grinding wheel manufacturing; polyamide resin has good toughness and wear resistance, and is suitable for grinding wheel materials requiring high toughness and impact resistance, such as heavy-load grinding; aralkylphenolic resin has good heat resistance and chemical stability, and can still maintain its performance at high temperatures, and is suitable for high-speed grinding and hard material processing. Preferably, the thermosetting resin particles are selected from phenolic resin. Phenolic resin is a commonly used thermosetting resin with the characteristics of high hardness and good heat resistance. Phenolic resin has high bonding strength, the grinding line speed can reach a higher range, and it can withstand greater grinding pressure. Therefore, it is widely used in occasions requiring heavy-load grinding, such as the steel industry.

[0064] In some embodiments, the inorganic filler is selected from one or more of iron sulfide, cryolite, potassium sulfate, calcium oxide, hemihydrate gypsum powder, corundum, silicon carbide powder, potassium fluoroborate, glass fiber, copper slag, inorganic oxides, zeolite, magnesium oxide, chromium oxide, graphite, molybdenum disulfide, and zinc oxide. Each of these inorganic fillers has unique properties, such as hardness, wear resistance, thermal conductivity, chemical stability, etc., and they can play multiple roles in resin grinding wheels. For example, hard fillers such as corundum and silicon carbide powder can enhance the grinding ability of the grinding wheel and improve grinding efficiency; while calcium oxide, hemihydrate gypsum powder, etc. may be used to adjust the hardness and porosity of the grinding wheel and improve the grinding performance; reinforcing materials such as glass fiber can improve the strength and toughness of the grinding wheel and extend its service life. Among these inorganic fillers, the specific type and proportion selected will depend on the required grinding wheel performance and application scenarios. For example, for a grinding wheel that requires high wear resistance and high thermal stability, high hardness corundum or silicon carbide powder may be selected as the main filler; for a grinding wheel that requires good self-sharpening and chip evacuation performance, a filler combination with a certain porosity and easy grindability may be selected.

[0065] In some embodiments, the inorganic filler is selected from a mixture of iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber, and the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 100:10-60:30-80:40-60:40-60. Preferably, the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 100:40-50:60-70:45-55:45-55. Specifically, the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 100:10:30:40:40, 100:35:55:50:50, 100:60:80:60:60, 100:10:55:50:50, 100:10:80:60:60, 100:35:30:40:40, 100:35:80:60:60, 100:60:55:50:50, 100:10:80:60:60, 100:35:30:40:40, 100:35:80:60:60, 100:60:30:40:40, 100:60:55:50:50, 100:10:3 0:40:40, 100:10:55:40:40, 100:60:55:60:60, 100:10:80:40:40, 100:35:55:40:50, 100:60:80:40:60, 100:35:55:60:50, 100:60:80:60:60, 100:35:55:50:40, 100:60:80:60:40, 100:35:55:50:60, 100:60:80:60:60.

[0066] In another embodiment of the present application, a method for preparing the resin grinding wheel material is provided, comprising the following steps:

[0067] S1: mixing thermosetting resin particles, inorganic fillers and curing agent, heating to a first temperature for melting and blending, and granulating to obtain powder; the first temperature is between the melting point of the thermosetting resin and the thermal curing temperature.

[0068] In this application, the melting point is the fixed temperature point at which the thermosetting resin changes from a stable crystalline state (i.e. solid state) to a liquid state (i.e. molten state) under standard atmospheric pressure. This temperature point indicates the destruction of the internal lattice structure of the thermosetting resin and the weakening of the interaction between molecules or atoms, allowing them to overcome the lattice constraints and enter a disordered liquid arrangement state.

[0069] In the present application, the thermosetting temperature is the temperature at which the thermosetting resin undergoes a chemical reaction and solidifies into a solid form. Before reaching this temperature, the resin remains in a liquid or molten state and can be mixed with other ingredients. Once the thermosetting temperature is reached or exceeded, the resin will begin to solidify and form a solid form.

[0070] In certain embodiments, weighed thermosetting resin particles, inorganic fillers and curing agents are placed in a mixing device for preliminary mixing. The mixing device may be a high-speed mixer, a planetary mixer, etc., to ensure that the materials are evenly dispersed. The mixture is heated to a first temperature, which is between the melting point of the thermosetting resin and the thermal curing temperature. The purpose of this step is to melt the resin particles, fully mix with the inorganic filler and curing agent, and form a uniform melt. The heating method may be electric heating, steam heating, or hot air heating. During the heating process, a stirrer or mixer is used to continuously stir the mixture to ensure that the resin, filler and curing agent are evenly mixed. At the same time, pay attention to controlling the heating rate and stirring speed to avoid overheating of the material or uneven curing. The melt blended material is cooled to an appropriate temperature for granulation. The cooling method may be natural cooling or forced cooling, such as using cooling water or a cooling fan. The cooled melt is granulated by a granulator. The granulator may be an extruder, a cutting type, or a tablet press type, etc., and a suitable granulation method is selected according to specific needs. During the granulation process, the temperature and pressure of the material must be controlled to ensure the quality of the powder. The powder is screened to remove particles that do not meet the requirements. The screened powder is collected and stored in a dry and cool place to avoid moisture and contamination.

[0071] In some embodiments, the thermosetting resin particles are selected from one or more of phenolic resin, epoxy resin, polyphthalonitrile resin, polyurethane resin, polyimide resin and aralkylphenolic resin; the inorganic filler is selected from one or more of iron sulfide, cryolite, potassium sulfate, calcium oxide, hemihydrate gypsum powder, corundum, silicon carbide powder, potassium fluoroborate, glass fiber, copper slag, inorganic oxide, zeolite, magnesium oxide, chromium oxide, graphite, molybdenum disulfide, zinc oxide; the curing agent is selected from one or more of hexamethylenetetramine, polyoxymethylene, alkaline thermosetting resin, epoxy resin.

[0072] In some embodiments, the first temperature is determined according to the selected thermosetting resin, and is between the melting point of the thermosetting resin and the thermal curing temperature. Taking the thermosetting resin as an example, the first temperature of the melting point matching is 100-120°C, and specifically, the first temperature can be 100°C, 102°C, 103°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C. The melting point of the selected phenolic resin is 65-110°C, preferably, the melting point is 70-90°C, and specifically, the melting point of the phenolic resin is 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 95°C, 100°C, 105°C, 110°C.

[0073] In this application, heat curing temperature refers to the temperature that a thermosetting resin reaches and maintains for a period of time under specific process conditions to promote a chemical reaction inside it, thereby achieving the temperature required for the curing reaction. The curing temperature is usually determined by measuring the heat released or absorbed by the sample during heating or cooling. During the test, a mixture of resin and curing agent is placed in a DSC instrument and heated at a certain heating rate. An exothermic peak will appear on the DSC curve, and the temperature range corresponding to the exothermic peak is the temperature interval where the curing reaction occurs. Usually, the starting temperature of the exothermic peak can be used as the heat curing temperature, and the peak temperature is near the temperature region where the curing reaction is most intense. The temperature in this region can be used as an important reference range for the optimal curing temperature.

[0074] S2: adding powder into abrasive at a third temperature, stirring until the powder is coated on the surface of the abrasive, cooling to a fourth temperature to break up and obtain abrasive particles coated with the powder; the third temperature is between the melting point and the thermal curing temperature of the thermosetting resin and is higher than the first temperature; the fourth temperature is equal to or lower than the melting point of the thermosetting resin.

[0075] In some embodiments, the abrasive of the third temperature refers to heating the abrasive body to a specific temperature, which is called the third temperature, and this temperature is between the melting point of the thermosetting resin and the thermal curing temperature, ensuring that the abrasive particles can both make the thermosetting resin in the powder reach a melted and softened state at the third temperature and avoid the occurrence of a curing and cross-linking reaction. When the abrasive particles with the third temperature are mixed with the powder, they can effectively transfer heat to the powder, causing the thermosetting resin material in the powder to melt and soften again, thereby achieving the coating of the abrasive particles. In the preparation process of the powder, the thermosetting resin material has undergone the initial melting and softening stage at the first temperature. This stage ensures that the resin material reaches a certain fluidity, which is convenient for subsequent processing. However, in the subsequent melting and coating process, in order to more effectively realize the combination of the powder and the abrasive particles, a third temperature is specially designed. This temperature is higher than the first temperature during the initial melting and softening, which further promotes the melting state of the thermosetting resin material and makes it reach a more sufficient softening degree. This measure not only enhances the fluidity of the resin, but also promotes the mutual penetration and diffusion between the resin molecules, thereby ensuring that the thermosetting resin in the powder can be more evenly coated on the surface of the abrasive particles. Usually, the third temperature is 10-50°C higher than the first temperature. Specifically, it can be 10°C, 15°C, 20°C, 25°C, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 45°C, 50°C higher than the first temperature. Taking phenolic resin as an example of thermosetting resin, the third temperature can be 130-150°C. For example, the third temperature can be 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C, or 150°C.

[0076] In some embodiments, the abrasive can be heated using a hot air furnace, an electric heating plate, a microwave heater, etc. The abrasive is accurately heated to the third temperature through a temperature sensor and a temperature control system. This usually involves a preheating process to ensure that the abrasive is maintained within this temperature range throughout the treatment process.

[0077] In certain embodiments, the stirring device can be stirred using equipment such as a mixer, a mixing barrel, a ball mill, etc. Preferably, a mixer is used for stirring, and the stirring rate is 30-80r / min and the stirring time is 2-7min. Specifically, the stirring rate is 30r / min, 34r / min, 38r / min, 42r / min, 46r / min, 50r / min, 54r / min, 58r / min, 62r / min, 66r / min, 70r / min, 74r / min, 78r / min, 80r / min. The stirring time is 2min, 3min, 4min, 5min, 6min, 7min.

[0078] In some embodiments, cooling to the fourth temperature can be performed by air cooling, water cooling, natural cooling, etc. The selection of an appropriate cooling method depends on factors such as the properties of the mixture, production efficiency, and cost. In the process of powder-coated abrasives, the cooling step plays a vital role, and its main purpose is to achieve effective dispersion of the abrasive particles after coating. In order to achieve this goal, a fourth temperature is set, which is selected to be equal to or lower than the melting point of the thermosetting resin. The purpose of cooling is to facilitate the dispersion of the abrasive coated with powder, so the fourth temperature is selected to be equal to or lower than the melting point of the thermosetting resin. At this time, the thermosetting resin of the powder has been cooled and hardened, and the materials are no longer adhered to each other, so that the coated abrasive particles can be more easily and evenly separated into individual particles. Preferably, the fourth temperature is slightly lower than the melting point of the thermosetting resin, usually 5 to 10°C, for example, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C. When the fourth temperature is precisely set within this range slightly below the melting point, the thermosetting resin undergoes a transition stage from melting to hardening. During this stage, the interaction between the resin molecular chains gradually increases, making the resin layer have higher mechanical strength and hardness. Since the temperature does not drop too low, the hardening process of the resin is relatively mild, avoiding internal stress or cracks caused by rapid cooling, and ensuring the integrity and durability of the coating layer. At the same time, this temperature setting ensures that the materials (i.e., the coated abrasive particles) will not stick together due to the incomplete hardening of the resin, thereby facilitating separation.

[0079] In some embodiments, mechanical or air flow breaking is adopted, and abrasive particles coated with powder are obtained by sieving. Breaking up means that the mixture that has been cooled to the fourth temperature is broken or dispersed into individual abrasive particles in a certain way, and the surface of these abrasive particles is evenly coated with powder. Equipment such as a vibrating screen, a disperser, and a crusher can be used for breaking up. These devices usually have adjustable amplitude, frequency, and dispersion force to meet different breaking up requirements. The sieve aperture is 2 to 12 meshes, preferably 4 to 8 meshes. Specifically, the sieve aperture can be 2 meshes, 4 meshes, 6 meshes, 8 meshes, 10 meshes, and 12 meshes.

[0080] In another embodiment of the present application, after the abrasive is heated to the second temperature, it is cooled to the third temperature; the second temperature is 160-190°C, for example, the second temperature can be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C, 190°C. During the production process, when stirring is started to prepare for adding the premix, there will be a cooling phenomenon. The cooling speed is different at different temperatures, so the temperature should be raised to a higher temperature and then cooled to give the premixed particles a time period to better ensure the stability of product quality.

[0081] In another embodiment of the present application, a method for preparing a heavy-load grinding wheel is provided, wherein the raw material of the heavy-load grinding wheel includes the resin grinding wheel material, and the resin grinding wheel material is pre-pressed to obtain a primary molded blank; the primary molded blank is preheated to 80-100°C, and the temperature is increased to 180-195°C to be pressed to obtain a molded grinding wheel; the molded grinding wheel is heat-cured to obtain the heavy-load grinding wheel.

[0082] In some embodiments, the resin grinding wheel material is placed in the inner cavity of the grinding wheel mold and spread evenly, and 4 to 10 MPa pre-pressure is applied to obtain a pre-molded blank. The blank with a certain shape and density is pressed by applying pressure, which lays the foundation for subsequent processing. The applied pressure needs to be precisely controlled to ensure the uniformity and stability of the blank. The density of the grinding wheel is too small and cannot be reached. A larger press is required for too large a grinding wheel, which is not economical. For example, the applied pressure can be 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, and 10 MPa.

[0083] In some embodiments, the preformed blank is preheated from room temperature to 80-100°C in 20-60 minutes. The specifications of the grinding wheel blank are usually large, with a thickness of about 100 mm and a diameter that may vary in a wide range of 450 to 920 mm. Such dimensional characteristics make the temperature difference between the inside and the surface of the blank a key factor that must be considered. If the blank is directly placed in a hot press for pressing at room temperature, due to the uneven heat transfer, the surface may quickly reach a state of melting and solidification, while the internal temperature is still far below the critical value of melting. This uneven temperature distribution can lead to a series of serious consequences. For example, the density inside the grinding wheel may not meet the design standard because the internal material fails to soften sufficiently to form a tight structure. The porosity may increase abnormally because the unmelted material inside cannot effectively discharge gas during the pressing process. These problems will not only significantly reduce the wear resistance and service life of the grinding wheel, but may also have a negative impact on its overall performance. Gradually increasing the overall temperature of the blank through the preheating step is the key to ensuring uniform distribution of temperature inside and on the surface of the grinding wheel and avoiding the above problems. For example, the preheating time window can be 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min, 31min, 32min, 33min, 34min, 35min, 36min, 37min, 38min, 39min, 40min, 42min, 44min, 46min, 48min, 50min, 52min, 54min, 56min, 58min, 60min; the final preheating temperature can be 80℃, 82℃, 84℃, 86℃, 88℃, 90℃, 92℃, 94℃, 96℃, 98℃, 99℃, 100℃.

[0084] In some embodiments, the molding grinding wheel pressing pressure is 10-20Mpa, preferably, it is pressed for 60-120min under 10-20Mpa pressure conditions. Specifically, the molding grinding wheel pressing pressure can be 10Mpa, 11Mpa, 12Mpa, 13Mpa, 14Mpa, 15Mpa, 16Mpa, 17Mpa, 18Mpa, 19Mpa, 20Mpa; the pressing time can be 60min, 63min, 66min, 69min, 72min, 75min, 78min, 81min, 84min, 87min, 90min, 93min, 96min, 99min, 102min, 105min, 108min, 111min, 114min, 117min, 120min.

[0085] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with specific embodiments.

[0086] Example

[0087] Resin grinding wheel material

[0088] Example 1

[0089] A resin grinding wheel material comprises 100 kg of abrasive particles and 40 kg of powder coated on the surface of the abrasive particles, wherein the powder comprises 13.3 kg of thermosetting resin particles and 26.7 g of inorganic filler.

[0090] The resin grinding wheel material is prepared by the following method: after thermosetting resin particles and inorganic fillers are mixed uniformly in proportion, curing agent hexamethylenetetramine is added, and the mixture is melt-blended at 100°C (first temperature), and granulated to obtain powder; abrasive particles according to the proportioned dosage are heated to 160°C (second temperature), placed in a mixer for stirring, and the temperature is detected at any time. When the temperature drops to 130°C (third temperature), the mixed powder is added, and stirring is continued. The state of the powder is observed during the stirring process until the powder is wrapped on the surface of the abrasive and the powder is not visible visually. Compressed air is introduced to cool the material to below 70°C (fourth temperature), and the material is discharged. When discharging the material, the abrasive particles adhering to each other are sieved through a 4-mesh vibrating screen to break up the abrasive particles, and the material is sieved through a 4-mesh screen, and the material is cooled to below 60°C for standby use.

[0091] Among them, the abrasive particles are 24# zirconium corundum.

[0092] The thermosetting resin particles are phenolic resin (Shandong Shengquan New Materials Co., Ltd., PF2700B), and the particle size D50 of the phenolic resin particles is 8 μm.

[0093] The inorganic filler is a mixture of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber, and the mass ratio of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 100:10:30:40:40; the particle size D50 of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 7 μm.

[0094] The curing agent is hexamethylenetetramine.

[0095] Example 2

[0096] The same as Example 1, except that: a resin grinding wheel material, including 100 kg of abrasive particles and 70 kg of powder coated on the surface of the abrasive particles, wherein the powder includes 11.7 kg of thermosetting resin particles and 58.3 g of inorganic filler.

[0097] Example 3

[0098] The same as Example 1, except that: a resin grinding wheel material includes 100 kg of abrasive particles and 55 kg of powder coated on the surface of the abrasive particles, wherein the powder includes 13.75 kg of thermosetting resin particles and 41.25 g of inorganic filler.

[0099] Example 4

[0100] The same as Example 1, except that: the abrasive particles are 6# zirconium corundum; the particle size D50 of the phenolic resin particles is 30 μm; the particle size D50 of iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 20 μm.

[0101] Example 5

[0102] The same as Example 1, except that: the abrasive particles are 15# zirconium corundum; the particle size D50 of the phenolic resin particles is 18 μm; the particle size D50 of iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 13 μm.

[0103] Example 6

[0104] The same as Example 1, except that in the preparation process: after the thermosetting resin particles and the inorganic filler are mixed uniformly in proportion, a curing agent is added, heated to 120°C (first temperature) for melt blending, and granulated to obtain a powder; the abrasive particles according to the proportioned dosage are heated to 190°C (second temperature), placed in a mixer for stirring, and the temperature is detected at any time. When the temperature drops to 150°C (third temperature), the mixed powder is added, and stirring is continued. The state of the powder is observed during the stirring process until the powder is wrapped on the surface of the abrasive and the powder is not visible visually. Compressed air is introduced to cool down, and the temperature is lowered to below 90°C (fourth temperature), and the material is discharged. When discharging, the abrasive particles adhering to each other are sieved through a 4-mesh vibrating screen to break up the abrasive particles, and the material is sieved through a 4-mesh screen, and the material is cooled to below 60°C for standby use.

[0105] Example 7

[0106] The same as Example 1, except that in the preparation process: after the thermosetting resin particles and the inorganic filler are mixed uniformly in proportion, a curing agent is added, heated to 110°C (first temperature) for melt blending, and granulated to obtain a powder; the abrasive particles according to the proportioned dosage are heated to 175°C (second temperature), placed in a mixer for stirring, and the temperature is detected at any time. When the temperature drops to 140°C (third temperature), the mixed powder is added, and stirring is continued. The state of the powder is observed during the stirring process until the powder is wrapped around the surface of the abrasive and the powder is not visible visually. Compressed air is introduced to cool down, and the temperature is lowered to below 80°C (fourth temperature), and the material is discharged. When discharging, the abrasive particles adhering to each other are sieved through a 4-mesh vibrating screen to break up the abrasive particles, and the material is sieved through a 4-mesh screen, and the material is cooled to below 60°C for standby use.

[0107] Example 8

[0108] A resin grinding wheel material comprises 100 kg of abrasive particles and 55 kg of powder coated on the surface of the abrasive particles, wherein the powder comprises 13.75 kg of thermosetting resin particles and 41.25 g of inorganic filler.

[0109] The resin grinding wheel material is prepared by the following method: after thermosetting resin particles and inorganic fillers are mixed uniformly in proportion, curing agent hexamethylenetetramine is added, and the mixture is melt-blended at 110°C (first temperature), and granulated to obtain powder; abrasive particles according to the proportioned dosage are heated to 175°C (second temperature), placed in a mixer for stirring, and the temperature is detected at any time. When the temperature drops to 140°C (third temperature), the mixed powder is added, and stirring is continued. The state of the powder is observed during the stirring process until the powder is wrapped on the surface of the abrasive and the powder is not visible visually. Compressed air is introduced to cool the material to below 80°C (fourth temperature), and the material is discharged. When discharging the material, the abrasive particles adhering to each other are sieved through a 4-mesh vibrating screen to break up the abrasive particles, and the material is sieved through a 4-mesh screen to cool the material to below 60°C for standby use.

[0110] Among them, the abrasive particles are 15# zirconium corundum.

[0111] The thermosetting resin particles are phenolic resin (Shandong Shengquan New Materials Co., Ltd., PF2700B), and the particle size D50 of the phenolic resin particles is 18 μm.

[0112] The inorganic filler is a mixture of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber, and the mass ratio of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 100:35:55:50:50; the particle size D50 of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 13 μm.

[0113] The curing agent is hexamethylenetetramine.

[0114] Example 9

[0115] The same as Example 1, except that the powder is directly heated to the third temperature, specifically: after the thermosetting resin particles and the inorganic filler are mixed evenly in proportion, a curing agent is added, and the mixture is heated to 100°C (the first temperature) for melt blending, and the powder is granulated; when the abrasive particles according to the proportion are heated to 130°C (the third temperature), the mixed powder is added, and stirring is continued. During the stirring process, the state of the powder is observed until the powder is wrapped on the surface of the abrasive and the powder is not visible. Compressed air is introduced to cool the material to below 70°C (the fourth temperature), and the material is discharged. When discharging the material, the material is sieved through a 4-mesh vibrating screen to break up the abrasives that stick together, and the material is sieved through a 4-mesh screen, and the material is cooled to below 60°C for standby use.

[0116] Example 10

[0117] The same as Example 1, except that the mass ratio of iron sulfide, cryolite, potassium sulfate, calcium oxide and glass fiber is 100:60:80:60:60.

[0118] Comparative Example 1

[0119] The same as Example 1, except that the abrasive particles are 30# zirconium corundum.

[0120] Comparative Example 2

[0121] The same as Example 4, except that the abrasive particles are 3# zirconia corundum.

[0122] Comparative Example 3

[0123] The same as Example 1, except for the third temperature in the preparation process, specifically: the abrasive particles according to the proportion of the dosage are heated to 160°C (the second temperature), placed in a mixer and stirred, and the temperature is detected at any time. When the temperature drops to 120°C (the third temperature), the mixed powder is added and continued to be stirred. The state of the powder is observed during the stirring process until the powder is wrapped around the surface of the abrasive and no powder can be seen visually.

[0124] Comparative Example 4

[0125] The same as Example 6, except for the third temperature in the preparation process, specifically: the abrasive particles according to the proportion of the dosage are heated to 190°C (the second temperature), placed in a mixer and stirred, and the temperature is checked at any time. When the temperature drops to 160°C (the third temperature), the mixed powder is added and continued to be stirred. The state of the powder is observed during the stirring process until the powder is wrapped around the surface of the abrasive and no powder can be seen visually.

[0126] Comparative Example 5

[0127] The same as Example 1, except that: a heavy-duty grinding wheel molding material, the raw materials include 100 kg of zirconium corundum, 13.3 kg of binder, and 26.7 kg of inorganic filler. Among them, the binder includes phenolic resin powder and a wetting agent, the phenolic resin powder is 8.71 kg, and the rest is the wetting agent, that is, the wetting agent is 4.59 kg.

[0128] The preparation method is as follows: put zirconium corundum into a mixing pot, then put a wetting agent into the mixing pot, and then start the first stirring. When the wetting agent wraps the abrasive mixture, the mixing pot stops stirring. Furthermore, the first stirring time is not less than 5 minutes, and then add thermosetting phenolic resin powder and inorganic filler into the mixing pot, and then start the second stirring. The second stirring time is not less than 7 minutes. After stirring evenly, add glass fiber with a length of 3 to 5 mm and mix for 1 to 2 minutes. Pour out the mixture in the mixing pot and store it in a constant temperature and humidity environment for use.

[0129] Wherein, the wetting agent liquid phenolic resin is (Shandong Shengquan New Materials Co., Ltd., PF2400).

[0130] The phenolic resin powder comes from Shandong Shengquan New Materials Co., Ltd. PF2700B, and the particle size D50 of the phenolic resin powder is 8 μm.

[0131] Table 1 Preparation conditions of Examples 1 to 10 and Comparative Examples 1 to 5

[0132]

[0133]

[0134] Experimental example

[0135] 10 g of the prepared resin grinding wheel material was placed in 100 g of hydrofluoric acid and boiled for 10 minutes. The mixed resin grinding wheel material was filtered and washed, and weighed after drying to detect the dissolution rate of the hydrofluoric acid on the resin grinding wheel material.

[0136] Table 2 Hydrofluoric acid dissolution rate

[0137] project Dissolution rate (%) Example 1 3.16 Example 2 3.12 Example 3 2.65 Example 4 2.96 Example 5 2.78 Example 6 2.54 Example 7 2.23 Example 8 1.9 Example 9 3.57 Example 10 3.08 Comparative Example 1 5.38 Comparative Example 2 6.22 Comparative Example 3 5.49 Comparative Example 4 4.87 Comparative Example 5 4.54

[0138] As can be seen from Table 2, the dissolution rates of the resin grinding wheel materials of Examples 1 to 10 of the present application are all below 4%. This data clearly indicates that the surface powder of the resin grinding wheel material in the present application achieves an excellent coating effect, thereby significantly improving the strength of the prepared grinding wheel. Specifically, the low dissolution rate indicates that a tight and effective bonding layer is formed between the powder and the abrasive particles, which helps to enhance the overall structural stability of the grinding wheel.

[0139] It is worth noting that in Example 9, due to the strategy of directly heating the abrasive particles to the third temperature and adding the powder at this temperature, the temperature of the mixed system is reduced. This temperature change has an adverse effect on the uniform coating of the powder on the abrasive surface, thereby affecting the final coating effect and the strength of the grinding wheel.

[0140] In addition, by comparing the data of the examples with the control group, we found that the size of the abrasive particle size has a direct effect on the dissolution rate and strength of the resin grinding wheel material. Specifically, the comparison between Comparative Example 1 and Example 1, and between Comparative Example 2 and Example 4 shows that when the abrasive particle size changes, the dissolution rate increases significantly, which indicates that the matching degree of the abrasive particle size, the resin particle size, and the inorganic filler particle size is crucial to achieve a good coating effect and the preparation of a high-strength grinding wheel.

[0141] At the same time, temperature control during powder coating is also a key factor affecting the coating strength of the resin grinding wheel material. As shown in Comparative Example 3 and Example 1, and Comparative Example 4 and Example 6, the selection of the coating temperature needs to be precisely controlled. When the temperature is too low, the resin is not fully melted and a good coating layer cannot be formed; while too high a temperature may cause the resin to solidify prematurely, which will also reduce the coating effect. Therefore, a suitable coating temperature is an important condition to ensure that the resin grinding wheel material has excellent coating strength and overall performance.

[0142] Comparative Example 5 adopts a different preparation method to obtain the resin grinding wheel mixture, specifically, the abrasive and the powder are mixed by a wetting agent, and the granulation step described in the present application is not used to form particles. Although this preparation method realizes the combination of abrasive and powder to a certain extent, its coating effect is obviously inferior to the method proposed in the present application. Specifically, in Comparative Example 5, although the addition of the wetting agent helps the mixing uniformity of the abrasive and the powder, due to the lack of the granulation step, the bonding force between the abrasive and the powder is relatively weak, and it is difficult to form a tight and firm coating layer. In contrast, the present application not only enhances the interaction force between the abrasive and the powder through the granulation step, but also makes the coating layer more uniform and dense, thereby significantly improving the overall strength and wear resistance of the resin grinding wheel material.

[0143] Heavy Duty Grinding Wheel

[0144] Application Examples 1 to 10

[0145] A method for preparing a heavy-load grinding wheel comprises the following steps:

[0146] S1 initial forming

[0147] The resin grinding wheel material is added with 4-5 mm chopped glass fibers accounting for 3% of the resin grinding wheel material, mixed evenly, placed in the inner cavity of the grinding wheel mold and spread evenly, and pre-pressed with 7 MPa for initial forming.

[0148] S2 Warm-up

[0149] Place the initially formed mold and blank in the drying oven and preheat to 90°C for 40 minutes.

[0150] S3 hot pressing

[0151] The preheated primary forming mold and blank are placed in a hot press with a template temperature of 190°C, and pressed at a pressure of 15Mpa for 90 minutes to obtain a hot-pressed grinding wheel. The air is released every 3 to 5 minutes in the early stage and every 10 minutes in the later stage.

[0152] S4 demoulding

[0153] The grinding wheel is demoulded and placed on a slide for heat curing.

[0154] S5 heat curing treatment

[0155] The hot-pressed grinding wheel was placed on an oven bracket and moved into the oven for staged temperature curing. The curing procedure of the heat curing treatment was as follows: room temperature; heating to 80°C for 60 minutes, keeping warm for 60 minutes; heating to 120°C for 60 minutes, keeping warm for 120 minutes; heating to 160°C for 60 minutes, keeping warm for 120 minutes; heating to 185°C for 60 minutes, keeping warm for 600 minutes; cooling to 80°C for 300 minutes.

[0156] Table 3 Application Examples 1 to 10 and Comparative Application Examples 1 to 5

[0157] Application Examples Application Example 1 Application Example 2 Application Example 3 Application Example 4 Application Example 5 Resin grinding wheel material Example 1 Example 2 Example 3 Example 4 Example 5 Application Examples Application Example 6 Application Example 7 Application Example 8 Application Example 9 Application Example 10 Resin grinding wheel material Example 6 Example 7 Example 8 Example 9 Example 10 Application Examples Comparative application example 1 Comparative Application Example 2 Comparative Application Example 3 Comparative Application Example 4 Comparative Application Example 5 Resin grinding wheel material Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5

[0158] Experimental example

[0159] Application Examples and Comparative Application Examples The grinding wheel has a diameter of 105 mm and a thickness of 3 mm.

[0160] 1) Rotational strength test

[0161] Application example and comparative application example The diameter of the grinding wheel is 105mm and the thickness is 3mm. According to the standard of "GB / T2493-2013 Grinding wheel rotation test method", the 45# steel bar is ground with the grinding wheel.

[0162] 2) Tensile strength test

[0163] A static tensile testing machine was used to apply tensile load to the grinding wheels of the corresponding application examples and the comparative application examples, and the maximum load before fracture was measured. The tensile speed was 5 mm / min.

[0164] 3) Grinding ratio

[0165] Clean the grinding wheel and carbide tool to be ground with acetone, put them in an oven, dry them at 80℃ for 1h, move them into a dryer to cool to room temperature, weigh and record. Then fix the grinding wheel and tool on the grinding tester, set the parameters, start grinding, and the tester stops automatically after the grinding process is completed. Grinding wheel speed: 5000r / min, loading pressure: 500g, constant force loading swing frequency: 20 times / min, carbide tool: YG8. Remove the ground grinding wheel and tool, clean them with acetone, put them in an oven, dry them at 80℃ for 1h, move them into a dryer to cool to room temperature, weigh and record, and calculate the grinding ratio.

[0166] Table 4 Heavy load grinding wheel performance test

[0167]

[0168] As can be seen from Table 4, the heavy-duty grinding wheel prepared by the resin grinding wheel material in the embodiment is highly consistent with the corresponding embodiment in terms of various performance trends. Specifically, the application examples corresponding to Examples 1 to 10 all show excellent performance, which is mainly reflected in two key indicators: tensile strength and grinding ratio. Tensile strength is an important indicator for measuring the internal bonding strength of the grinding wheel material, which reflects the ability of the grinding wheel to resist fracture when subjected to external force. In the application examples, all heavy-duty grinding wheels prepared based on the resin grinding wheel materials of Examples 1 to 10 showed high tensile strength, which means that these grinding wheels can better withstand the huge pressure and impact force generated during the grinding process during use, thereby extending the service life of the grinding wheel. On the other hand, the grinding ratio is an important indicator for evaluating the grinding efficiency and economy of the grinding wheel, which represents the ratio of the ability of the grinding wheel to grind the workpiece material per unit time to the consumption of the grinding wheel itself. In the application examples, these heavy-duty grinding wheels also show excellent grinding ratios, indicating that they can remove the workpiece material with higher efficiency during the grinding process while maintaining low grinding wheel consumption, thereby improving the economy and efficiency of the grinding operation.

[0169] 4) Grinding wheel cross-section morphology

[0170] like Figure 1 As shown, part a in the figure shows the broken cross-sectional morphology of the grinding wheel in application example 8 of the present application, while part b shows the broken cross-sectional morphology of the grinding wheel in comparative application example 5. Through comparative analysis, the difference between the two can be clearly seen: in application example 8 (Figure a), the number of broken cross-sectional surfaces of the grinding wheel is large, and these cross-sectional surfaces are uniformly distributed as a whole. This uniform cross-sectional distribution suggests that the bonding force between the resin grinding wheel materials inside the grinding wheel is relatively strong, and the dispersion state of these materials in the grinding wheel is also quite uniform. In contrast, in comparative application example 5 (Figure b), the number of broken cross-sectional surfaces of the grinding wheel is significantly reduced, and the distribution of these cross-sectional surfaces appears to be uneven, with obvious local concentration or sparseness. This uneven cross-sectional distribution means that the bonding force between the resin grinding wheel materials inside the grinding wheel is relatively weak, or the dispersion state of these materials in the grinding wheel is not ideal.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A resin grinding wheel material, comprising abrasive particles and powder coated on the surface of the abrasive particles, wherein the powder raw material comprises thermosetting resin particles and inorganic fillers.

2. The resin grinding wheel material according to claim 1, wherein the powder is obtained by melt-blending and granulating the thermosetting resin particles and the inorganic filler.

3. A resin grinding wheel material according to claim 2, wherein the temperature of the melt blending is between the melt softening temperature and the thermal curing temperature of the thermosetting resin particles.

4. A resin grinding wheel material according to claim 1, comprising 100 parts of abrasive particles and 40 to 70 parts of powder by weight; preferably, the resin grinding wheel material comprises 100 parts of abrasive particles and 55 parts of powder by weight.

5. The resin grinding wheel material according to claim 1, wherein the mass ratio of the thermosetting resin particles to the inorganic filler is 10:20-50; preferably, the mass ratio of the thermosetting resin particles to the inorganic filler is 10:

30.

6. A resin grinding wheel material according to claim 1, wherein the particle size of the abrasive particles is 6-24#, the particle size D50 of the thermosetting resin particles is 6-30μm, and the particle size D50 of the inorganic filler is 7-20μm; preferably, the particle size of the abrasive particles is 8-20#, the particle size D50 of the thermosetting resin particles is 10-20μm, and the particle size D50 of the inorganic filler is 8-15μm.

7. A resin grinding wheel material according to claim 1, wherein the abrasive particles are selected from one or more of brown corundum, white corundum, black silicon carbide, green silicon carbide, cubic boron nitride, chrome corundum, single crystal corundum, microcrystalline corundum, zirconium corundum, and ceramic corundum; The thermosetting resin particles are selected from one or more of phenolic resin, epoxy resin, polyphthalonitrile resin, polyurethane resin, polyimide resin and aralkylphenolic resin; The inorganic filler is selected from one or more of iron sulfide, cryolite, potassium sulfate, calcium oxide, hemihydrate gypsum powder, corundum, silicon carbide powder, potassium fluoroborate, glass fiber, copper slag, inorganic oxides, zeolite, magnesium oxide, chromium oxide, graphite, molybdenum disulfide, and zinc oxide; preferably, the inorganic filler is selected from a mixture of iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber, and the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 100:10-60:30-80:40-60:40-60; preferably, the mass ratio of the iron sulfide, cryolite, potassium sulfate, calcium oxide, and glass fiber is 100:40-50:60-70:45-55:45-55.

8. The method for preparing the resin grinding wheel material according to claim 1, comprising: Adding a curing agent to the thermosetting resin particles and the inorganic filler, heating them to a first temperature for melting and blending, and granulating them to obtain a powder; The first temperature is between the melting point and the thermal curing temperature of the thermosetting resin; Putting the powder into the abrasive at the third temperature, stirring until the powder is coated on the surface of the abrasive, cooling to a fourth temperature to disperse and obtain abrasive particles coated with the powder; the third temperature is between the melting point of the thermosetting resin and the thermal curing temperature and is higher than the first temperature; the fourth temperature is equal to or lower than the melting point of the thermosetting resin; Preferably, the third temperature is 10 to 50° C. higher than the first temperature; Preferably, the fourth temperature is equal to the melting point of the thermosetting resin particles; Preferably, after heating the abrasive to the second temperature, the abrasive is cooled to the third temperature; Preferably, the second temperature is 160-190°C.

9. A heavy-load grinding wheel, wherein the raw material of the heavy-load grinding wheel comprises the resin grinding wheel material according to any one of claims 1 to 7 or the resin grinding wheel material prepared by the preparation method according to claim 8.

10. The method for preparing the heavy-duty grinding wheel according to claim 9, comprising: Pre-pressing the resin grinding wheel material to obtain a primary blank; Preheating the preformed blank to 80-100° C., heating it to 180-195° C., and pressing it to obtain a formed grinding wheel; The molded grinding wheel is subjected to thermal curing treatment to obtain the heavy-load grinding wheel.